Una aproximación al amor en la filosofía de Baruch Spinoza - Tapia, Danilo (2021)
This paper offers an analysis of Spinoza’s concept of love based on the Treatise on the Emendation of the Intellect, the Short Treatise on God and the Ethics. Spinoza’s concept of love must be understood within his critical phenomenology of affects and his theory of knowledge. Thus understood, Spinoza’s concept of love entails that how we love —actively or passively— is more important than any normative distinction among objects of love. This reading of Spinoza’s concept of love is compatible with his ethical premises and his ontological monism, and with his understanding of love as an activity of the Substance.